DETERMINATION OF SPIROMESIFEN, QUINOLPHOS, MONOCROTOPHOS, CARBENDAZIM AND ACEPHATE RESIDUE BEHAVIOUR IN OKRA (ABELMOSHUS ESCULENTUS) BY LIQUID CHROMATOGRAPHY AND MASS SPECTROPHOTOMETRY AND THEIR DECONTAMINATION USING HOUSE HOLD PROCESSES - MUPPALLA, HYMAVATI; PEDDI, KIRANMAYI (International Journal of Applied Pharmaceutics, 2020)
Objective: Field experiments were conducted at Agricultural University, Rajendra Nagar, Hyderabad, Telanagana to study the dissipation kinetics of carbendazim, monocrotophos, spiromesifen, acephate and quinalphos in okra fruit. Decontamination study was also conducted to evaluate quality of okra pods by reducing the residues of carbendazim, monocrotophos, spiromesifen, acephate and quinalphos by using different processes such as 2% salt solution, acetic acid, biowash, butter milk, cooking, drying, Formula 1(T7), frying, lemon water, sodium bicarbonate, tamarind water and tap water. Methods: All the pesticide residues with one test dose at two spray i.e., first spray at flowering stage and second spray after an interval of ten days was carried out. The samples drawn at specific periods were analyzed by liquid chromatography and mass spectrophotometry (LC-MS/MS). Results: The initial deposit of carbendazim, monocrotophos, spiromesifen, acephate and quinalphos in okra was found to be 2.239, 2.586, 2.401, 1.39, 0.78 mg/kg respectively. More than 98 % of carbendazim, spirofesifin, acephate and quinolphos dissipated after 15 d and monocrotophos was dissipated after 10 d. Sodium bicarbonate and 2% salt solution are the best methods for decontamination after cooking. The decontamination values of frying and formula 1 seems to be almost same. After these two methods biowash thought to be the method of choice. Conclusion: These results are helpful in setting up maximum residual limit (MRLs) of these pesticides in okra in India. From the results, it could be recommended that cooking suits best for almost all of the pesticide residues.